Continuous Microfiber Wire Mandrel‐Less Biofabrication for Soft Tissue Engineering Applications. Issue 13 (29th April 2022) - Adamo, Arianna; Bartolacci, Joseph G.; Pedersen, Drake D.; Traina, Marco G.; Kim, Seungil; Pantano, Antonio; Ghersi, Giulio; Watkins, Simon C.; Wagner, William R.; Badylak, Stephen F.; D'Amore, Antonio
Abstract: Suture materials are the most common bioimplants in surgical and clinical practice, playing a crucial role in wound healing and tendon and ligament repair. Despite the assortment available on the market, sutures are still affected by significant disadvantages, including failure in mimicking the mechanical properties of the tissue, excessive fibrosis, and inflammation. This study introduces a mandrel‐less electrodeposition apparatus to fabricate continuous microfiber wires of indefinite length. The mandrel‐less biofabrication produces wires, potentially used as medical fibers, with different microfiber bundles, that imitate the hierarchical organization of native tissues, and tailored mechanical properties. Microfiber wire morphology and mechanical properties are characterized by scanning electron microscopy, digital image processing, and uniaxial tensile test. Wires are tested in vitro on monocyte/macrophage stimulation and in vivo on a rat surgical wound model. The wires produced by mandrel‐less deposition show an increased M2 macrophage phenotype in vitro. The in vivo assessment demonstrates that microfiber wires, compared to the medical fibers currently used, reduce pro‐inflammatory macrophage response and preserve their mechanical properties after 30 days of use. These results make this microfiber wire an ideal candidate as a suture material for soft tissue surgery, suggesting a crucial role of microarchitecture in more favorable host response. Abstract : This study introduces a novel mandrel‐less fabrication methodology for polymeric wires, with a circular cross‐section, unlimited length, and controllable microarchitecture. The use of this fabrication apparatus allows for the production of microfiber bundles with tunable ultrastructure and mechanical properties that can be used as suture materials and as tissue surrogates for tendon and ligaments repair.